Pengaruh Pemberian Pakan Cacing Sutra Terhadap Pertumbuhan Benih Ikan Koi (Cyprinus Rubrofuscus) - Afandi, Achmad Mujamil; Ainiyah, Roisatul; Izzah, Nikmatul; Ikerismawati, Senja (CV. SINAR HOWUHOWU, 2025)
This study aimed to evaluate the effect of silk worm (Tubifex sp.) feed on the growth performance and survival rate of koi fish (Cyprinus rubrofuscus) fry. The experiment was conducted in May 2025 at Yudharta University of Pasuruan using a Completely Randomized Design (CRD) with four treatments and four replications, namely P0 (100% pellet), P1 (95% pellet + 5% silk worm), P2 (90% pellet + 10% silk worm), and P3 (85% pellet + 15% silk worm). The observed parameters included length growth, weight growth, survival rate, Feed Conversion Ratio (FCR), and water quality. The results showed that the addition of silk worm feed had no significant effect on the length growth of koi fry (p>0.05), although P1 produced the highest average length. Weight growth was also not significantly different among treatments (p>0.05), with the best results observed in P0 (100% pellet) and P1 (95% pellet + 5% silk worm). The highest survival rate was recorded in P2 (90%) while the best FCR value was found in P0 (2.37). Water quality parameters such as temperature, pH, dissolved oxygen (DO), and total dissolved solids (TDS) remained within the optimal range throughout the study. In conclusion, the combination of pellet feed with silk worm has the potential to improve the survival rate of koi fry, but it does not significantly affect growth in length and weight. The optimal proportion of silk worm in the diet was found to be around 5–10%, while pellets remain the most efficient feed component to support biomass growth of koi fry.